The effect of physical activity counseling on diabetics' mobility : results of a secondary analysis - Randolph, Amanda (2013)
The preservation of mobility is essential for maintaining an independent and active lifestyle in old age. However, diabetes greatly increases older people’s susceptibility to mobility loss, leading to an increased risk of dependence. Given the increased prevalence of diabetes with age, and the increasing incidence of the disease worldwide, public health initiatives for preventing mobility loss with age must also prove effective for diabetics.